ANALISA STRATEGI PEMILIHAN MATERIAL PASANGAN DINDING - Retna Hapsari Kartadipura (INFO-TEKNIK, 2013)
Wall materials continue to evolve with the demands in achieving the cost, time, quality is the most effective and efficient. The emergence of technology as a light brick wall provides enough material positive impact on society in general and in particular the construction world. This study aims to analyze the material selection strategy that wall pair gain competitive advantage and have the product in accordance with the wishes of consumers and optimal support of existing resources.Light brick is divided into two types, namely lightweight autoclaved Aerated Concrete brick (AAC) and lightweight brick Cellular Lightweight Concrete (CLC), the second type of brick is made of lightweight cement-based materials and sand, which is different is the composition and method of manufacture, light brick AAC dipabrik made through the fabrication process, while the lightweight brick CLC not through the fabrication process.From the analysis, unit price pair of red brick wall USD 101 602 / m², light AAC brick wall USD 123 700 / m², lightweight brick wall CLC Rp 106.700 / m². The results of the three brick lightweight AAC and CLC types are more expensive than the red brick, this is light brick unit price is more expensive than red brick. But in terms of execution time using a lightweight brick 2x faster than using red brick. With SWOT analysis obtained material selection strategy that couples the wall as desired by consumers desired excellence and optimal support of existing resources. So to use the materials in the project planning and it all depends on where the material needs required.